Global Competition, Institutions, and the Diffusion of Organizational Practices: The International Spread of ISO 9000 Quality Certificates - Guler, Isin; Guillén, Mauro F.; Macpherson, John Muir (Administrative Science Quarterly, 2002)
We use panel data on ISO 9000 quality certification in 85 countries between 1993 and 1998 to better understand the cross-national diffusion of an organizational practice. Following neoinstitutional theory, we focus on the coercive, normative, and mimetic effects that result from the exposure of firms in a given country to a powerful source of critical resources, a common pool of relevant technical knowledge, and the experiences of firms located in other countries. We use social network theory to develop a systematic conceptual understanding of how firms located in different countries influence each other's rates of adoption as a result of cohesive and equivalent network relationships. Regression results provide support for our predictions that states and foreign multinationals are the key actors responsible for coercive isomorphism, cohesive trade relationships between countries generate coercive and normative effects, and role-equivalent trade relationships result in learning-based and competitive imitation.